Use of poly(ethylene naphthalate) as a self-vetoing structural material. (February 2020) - Efremenko, Y; Fajt, L; Febbraro, M; Fischer, F; Guitart, M; Hackett, B; Hayward, C; Hodák, R; Majorovits, B; Manzanillas, L; Muenstermann, D; Öz, E; et al.
Abstract: Poly(ethylene naphthalate), PEN, is an industrial polyester which has been shown to scintillate in the blue wavelength region. Combined with measurements of a high intrinsic radiopurity, this has sparked interest in the material for use in low-background experiments.